1939
DOI: 10.1002/j.1537-2197.1939.tb12880.x
|View full text |Cite
|
Sign up to set email alerts
|

The Cause of Natural Parthenocarpy

Abstract: GUSTAFSON-NATURAL PARTHENOCARPY 135 Beitrag zur Lehre von del' Constitution del' Losungen. Ann. Phys. u. Chern. .sci!: 166-190. IEI.SEN, N. 19:24. Studies on the transmission of stimuli in the coleoptile of Avena. Dansk Bot. AI'. 4: 1-45. OII()I.~I, L. W. 1910. Die freie Diffusion del' Nichtelektrolyte. I. trber hydrodiffusion einiger optisch aktlven Substanzen. Zeltschr, Physiol. Chern. 70: 378-407.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
1

Year Published

1939
1939
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(25 citation statements)
references
References 9 publications
1
23
0
1
Order By: Relevance
“…Severa1 lines of evidence suggest a correlation between increased auxin and gibberellin levels in the ovary before fertilization and parthenocarpic fruit development. For example, the endogenous levels of auxins and gibberellins are higher in ovaries of parthenocarpic tomato lines than in normal (i.e., seed-producing) lines (Gustafson, 1939b;Nitsch et al, 1960;Mapelli et al, 1979;Mapelli and Lombardi, 1982). In addition, the application of auxins or gibberellins to the outside of the ovary before fertilization often results in parthenocarpic fruit development.…”
Section: Phase I: Ovary Development Fertilization and Fruit Setmentioning
confidence: 99%
“…Severa1 lines of evidence suggest a correlation between increased auxin and gibberellin levels in the ovary before fertilization and parthenocarpic fruit development. For example, the endogenous levels of auxins and gibberellins are higher in ovaries of parthenocarpic tomato lines than in normal (i.e., seed-producing) lines (Gustafson, 1939b;Nitsch et al, 1960;Mapelli et al, 1979;Mapelli and Lombardi, 1982). In addition, the application of auxins or gibberellins to the outside of the ovary before fertilization often results in parthenocarpic fruit development.…”
Section: Phase I: Ovary Development Fertilization and Fruit Setmentioning
confidence: 99%
“…They demonstrated the presence of several types of auxins in nearly mature grapes (14) and made a comparative study of auxin changes during the development of berries of seeded and seedless Concord (16). Gustaf-son's comparison of auxins in seeded and seedless grapes was made on flowers before anthesis (6). Ferenczy (5) showed the presence of an auxin, possibly IAA4, in the juice of ripe grapes.…”
Section: Relationship Of Growth and Development To Changes In Sugarsmentioning
confidence: 99%
“…Moreover, the expression of auxin-induced gene in green sector of silenced fruit also decreased more than that in control fruit ( Figure 2G), which indicated again that the auxin accumulation was indeed reduced. The reports that higher endogenous levels of auxin in the ovaries of parthenocarpic tomato lines than in that of normal lines (Gustafson 1939;Nitsch et al 1960;Mapelli and Lombardi 1982) and the inducing of parthenocarpic fruit development by applying auxin transport inhibitor chloroflurenol to cucumber flowers (Robinson et al 1971), suggested that the auxin transport might be an important factor in parthenocarpic fruit development. Furthermore, indirect evidence has shown that the EIN2 was involved in the transport of auxin in Arabidopsis (Fujita and Syono 1996).…”
mentioning
confidence: 99%